ALIRAN DAN TOKOH-TOKOH FILSAFAT ISLAM - Nafsiyah, Faizatun; Hasniah, Hasniah; Nursalim, Eko; Khojir, Khojir (Al-Rabwah, 2025)
This article examines essential figures in Islamic philosophy who have played a crucial role in developing Islamic philosophical thought in the Islamic world. In its writing, this article employs a particular kind of library research with a descriptive-qualitative approach to analyze the schools and figures of philosophy in Islam. The study's findings indicate that Islamic philosophy emerged as a result of a dialogue between Islamic teachings and Greek philosophical traditions, giving birth to various schools that reflect diverse perspectives on fundamental issues such as Dialectical Theology (Kalam Science), Peripatetic (Masya'i), Illumination (Isyraqi), Irfani (Sufism), and Hikmah Muta'aliyah philosophy. Each school has different characteristics and philosophical outlooks, but all contributed to intellectual progress in the Islamic world. In addition, this article also discusses the role of central figures of Islamic philosophers such as Al-Kindi, Al-Farabi, Ibn Sina, Al-Ghazali, Suhrawardi, and Mulla Sadra, each of whom brought great contributions to Islamic philosophical thought. They played an essential role in shaping these schools with their profound thoughts regarding the connection between revelation, reason, God, and humanity. Understanding these schools and figures is hoped to provide more comprehensive information about Islamic philosophy's contribution to the context of global thought